The qualitative evidence-base of relationally-orientated therapy: A critical celebration - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2023)
In this article, I celebrate and critique the evidence base for relationally-orientated therapy. The central role played by the therapeutic relationship in effective therapy is now supported by an impressive evidence base, but it is mostly quantitative evidence that is privileged. This article attempts a small corrective to widen the lens by presenting 5 categories of qualitative evidence: Qualitative meta-analyses of client experiences of therapy; case studies; qualitative studies of clients’ experience; qualitative studies of therapists’ experience; and discursive studies of interactions and language use. The richness, relevance, and resonance of qualitative methodology is demonstrated by exemplar studies which highlight a special role for exploring under researched areas. However, qualitative researchers face confounding epistemological and methodological challenges in trying to capture the impossible complexity, ambivalence, variability, and ambiguity of relational therapy experiences across different cultural contexts. No methodology (qualitative, quantitative or mixed) can hope to do justice to these questions on its own and both critical reflexivity and humility are needed.